Alpha gliadin antibody levels: a serological test for coeliac disease. Issue 6383 (25th June 1983) - O'Farrelly, C; Kelly, J; Hekkens, W; Bradley, B; Thompson, A; Feighery, C; Weir, D G
Abstract : The diagnostic value in coeliac disease of circulating antibodies to casein, crude gliadin, and alpha gliadin was assessed using an adaption of the enzyme linked immunosorbent assay system. alpha Gliadin was the only antigen which consistently separated 26 patients with untreated coeliac disease from 26 normal controls and 13 patients with chronic inflammatory bowel disease. The mean assay index for the 26 patients was 3.1 (SD 1.2) compared with 1.05 (0.5) for the normal controls and 1.1 (0.6) for patients with chronic inflammatory bowel disease. The alpha gliadin antibody levels of six patients with coeliac disease who had maintained a gluten free diet for at least two years were not significantly higher than normal (1.0 (0.4)). The validity of the test was determined in 90 consecutive patients who were being investigated for the presence of coeliac disease. Levels of alpha gliadin antibody were raised in 36 out of 44 patients found to have histologically proved coeliac disease and in six out of 46 subjects whose jejunal mucosa was normal. Serial alpha gliadin concentrations were measured in 12 patients with coeliac disease who had repeat jejunal biopsies performed six months after starting a gluten free diet. The levels of antibody fell in seven of the eight patients whose jejunal mucosa improved on maintaining the diet. They remained raised in four patients who did not adhere to the diet and whose mucosa did not improve. Although a test measuring alpha gliadin antibodies is unlikely to replace jejunal biopsy in the diagnosis of coeliac disease it may be useful in screening for the disease among outpatients.